Regulating Crypto Payments to Prevent Money Laundering in Indonesia: A Comparative Study - Muhammad Sulton Ibnu Aulia Adhan; Nur Fadiah Anisah; Rusmilawati Windari (University of Jember, Indonesia, 2026)
The development of cryptocurrencies as part of digital financial innovation has created new challenges for anti-money laundering (AML) regulation and Digital Asset Supervision. In Indonesia, cryptocurrencies are legally recognised as digital financial assets under the supervision of the Financial Services Authority (OJK) after the 2025 digital financial assets regulatory reform. However, they are still prohibited from being used as a means of payment under Law Number 7 of 2011 on currencies. This dualism of regulation creates legal uncertainty and increases the risk of money laundering, as transactions can shift to less supervised channels, including peer-to-peer (P2P) transactions, decentralised finance (DeFi), and offshore platforms outside domestic supervision. This study aims to analyse cryptocurrency regulation in relation to money laundering in Indonesia and compare it with regulatory approaches in the United States and Singapore. This research uses a normative juridical method with legislative, comparative, and conceptual approaches. The United States and Singapore were chosen because they represent different but influential regulatory models. The United States implements a multi-regulatory, risk-based framework through FinCEN, the SEC, the CFTC, and OFAC. In contrast, Singapore implements a single, more integrated regulatory model through the Monetary Authority of Singapore (MAS) under the Payment Services Act (PSA). The results showed that Singapore's integrated model provided stronger regulatory coherence and supervisory efficiency, while the United States demonstrated higher adaptability to technological developments. Therefore, Indonesia needs to strengthen regulatory harmonisation, expand supervision of P2P and DeFi activities, implement domestic Travel rules, and improve coordination among OJK, Bank Indonesia, and PPATK to build a more integrated digital asset anti-money-laundering system.